Protein-energy adequacy and nutritional evolution of preterm infants in neonatal intensive care unit - HOLZBACH, Luciana Carla; Andrade de Medeiros MOREIRA, Renata; Junqueira PEREIRA, Renata (Revista de Nutrição, 2023)
Objective To evaluate the prescription of protein-calorie nutrition and its adequacy to the requirements of preterm newborns. Methods Prospective study with 30 preterm infants from a neonate intensive unit care. Anthropometric and nutritional therapy data were collected daily. Nutritional demands were defined according to the national guidelines. Protein-calorie nutritional support was considered adequate when it reached 70% of the calculated demand. The evolution of nutritional status was evaluated according to the growth curves of preterm infants. Statistical analyses were performed with the Statistical Package for Social Sciences 20.0, at a 5% significance level. Results The means of demand, prescription and infusion significantly differed from each other. The values of calories and proteins prescribed and infused were inadequate according to the calculated ones. There was no significantdifference etween the volume of prescribed and administered nutrition (p>0.05). At birth, 30% of the children were small, 66.7% were adequate, and 3.3% were large for gestational age. At discharge, the percentages were 33.3%; 63.3%; 3.3%, respectively. The values at birth significantly differed from those at discharge (p<0.01). Conclusion In the Unit of Neonatal Care studied, inadequate nutrient prescription and support is a factor that can compromise the nutritional status of the newborns at hospital discharge.